2021
DOI: 10.3389/fmed.2021.649979
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Refractory Diabetic Macular Edema Switch From Ranibizumab to Dexamethasone Implant and the Influential Factors: A Retrospective Real World Experience

Abstract: Introduction: To evaluate the effectiveness and safety of intravitreal dexamethasone (DEX) implants in refractory diabetic macular edema (DME) treated by intravitreal ranibizumab.Materials and Methods: We retrospectively analyzed DME patients who received DEX implant treatment after being refractory to at least 3 monthly intravitreal ranibizumab injections. The main outcomes were best-corrected visual acuity (BCVA), central retinal thickness (CRT), and intraocular pressure (IOP).Results: Twenty-nine eyes of 26… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Regarding the anatomic outcomes, our study found a significant reduction in CRT, without differences between groups. These findings are in agreement with the current evidence [ 19 , 20 , 33 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding the anatomic outcomes, our study found a significant reduction in CRT, without differences between groups. These findings are in agreement with the current evidence [ 19 , 20 , 33 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…The results of these studies point in the same general direction, indicating that in patients who did not adequately respond to anti-VEGF therapy, switching to DEX-i provides better functional and anatomical outcomes [ 19 , 20 , 33 36 ].…”
Section: Discussionmentioning
confidence: 92%
“…More importantly, we performed multivariate analysis and lens status was not significantly associated with outcomes. Previous studies have found similar conclusions that the lens status was not significantly associated with differences in BCVA ( 10 , 27 ). Lastly, if we had divided our subjects into two groups, the smaller case number in each group would make the outcomes less reliable.…”
Section: Discussionsupporting
confidence: 71%
“…The biodegradable intravitreal dexamethasone (DEX) implant (Ozurdex ® , Allergan, Inc., Irvine, CA, United States) has been identified as an effective treatment of DME and is approved by the US Food and Drug Administration (FDA) ( 9 ). In addition, the beneficial effects of DEX implant in anti-VEGF non-responders are well-established in several studies ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 95%
“…Other studies performed consecutive anti-VEGF injections (range 3 to 8) and then evaluated the responsiveness 12,13,30,31 . Consecutive injection without evaluation of treatment effect could lead to unnecessary injection and increased financial burden for the patient.…”
Section: Discussionmentioning
confidence: 99%